2010
DOI: 10.3904/kjim.2010.25.4.408
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Observation without Repeated Radioiodine Therapy in Differentiated Thyroid Carcinoma Patients with Positive Surveillance Whole-Body Scans and Negative Thyroglobulin

Abstract: Background/AimsCurrently, there is no consensus on the necessity of repeated radioiodine therapy (RAI) in patients who show iodine uptake in the thyroid bed on a diagnostic whole-body scan (DxWBS) despite undetectable thyroglobulin (Tg) levels after remnant ablation. The present study investigated the clinical outcomes of scan-positive, Tg-negative patients (WBS+Tg-) who did or did not receive additional RAI.MethodsWe retrospectively reviewed 389 differentiated thyroid carcinoma patients who underwent a total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…We previously reported that in DTC patients who previously had total thyroidectomy and high-dose RI remnant ablation, thyroid bed RI uptake at the postoperative 6- to 12-month whole-body scan showed a close association with higher TgAb levels, compared to no thyroid bed uptake [ 44 ]. Dewi et al [ 45 ] also reported that higher post-RI TgAb levels were significantly correlated with unsuccessful RI therapy (OR, 5.379; p = 0.007), which indicates that TgAb could serve as a surrogate marker for successful RI.…”
Section: Postoperative Tgab Follow-upmentioning
confidence: 99%
“…We previously reported that in DTC patients who previously had total thyroidectomy and high-dose RI remnant ablation, thyroid bed RI uptake at the postoperative 6- to 12-month whole-body scan showed a close association with higher TgAb levels, compared to no thyroid bed uptake [ 44 ]. Dewi et al [ 45 ] also reported that higher post-RI TgAb levels were significantly correlated with unsuccessful RI therapy (OR, 5.379; p = 0.007), which indicates that TgAb could serve as a surrogate marker for successful RI.…”
Section: Postoperative Tgab Follow-upmentioning
confidence: 99%
“…After radioiodine therapy, if there was no evidence of disease ( 131 I whole-body scan negative, stimulated thyroglobulin (Tg) Ͻ2 g/L, and absence of anti-Tg antibody), the patient was considered to be cured. A positive whole-body scan and/or stimulated Tg levels above 5 to 10 g/L were considered to indicate the presence of residual or recurrent tumor, 14 and the patients were considered to be noncured. Clinical history, pathologic findings, radioiodine therapy, and follow-up information were collected.…”
Section: Patients and Samplesmentioning
confidence: 99%
“…Occasionally, during follow‐up of thyroid cancer patients, clinicians encounter the combination of a positive stimulated post‐therapy or diagnostic whole‐body I‐131 scan but negative (undetectable) serum Tg/TgAb levels 6–8 . The precise frequency and implications of such a scenario, however, remain unclear.…”
Section: Introductionmentioning
confidence: 99%